2022
DOI: 10.1155/2022/6469217
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Intelligent Recommendation Model of E-Commerce Commodity Based on Feature Selection and Deep Belief Network

Abstract: Due to the complexity and uncertainty of customer demand behavior, it was often difficult to obtain satisfactory recommendation results by using the existing online commodity recommendation systems. Therefore, a network commodity intelligent recommendation model based on feature selection and deep belief network was proposed. Based on the basic structure and function of the existing recommendation systems, this paper expounded the interaction process between customers, e-commerce platforms, enterprises, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In 2022, Li, Y., et.al, [24] have presented Research on Intelligent Recommendation Model of E-Commerce Commodity Depend on Feature Selection with Deep Belief Network. Here, described the way in which consumers, businesses, e-commerce sites, and systems for recommendation the correlation concept between consumer demand and product recommendation was built through a study of the internal connection between both of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2022, Li, Y., et.al, [24] have presented Research on Intelligent Recommendation Model of E-Commerce Commodity Depend on Feature Selection with Deep Belief Network. Here, described the way in which consumers, businesses, e-commerce sites, and systems for recommendation the correlation concept between consumer demand and product recommendation was built through a study of the internal connection between both of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Model of E-Commerce Commodity Based on Feature Selection and Deep Belief Network" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Security and Communication Network Has Retracted The Article...mentioning
confidence: 99%